Dinamika Tasybīh dalam Retorika Arab sebagai Representasi Imajinatif dalam Wacana Modern - Dikwan, Ivananda; Maghfirah, Tadzkiratul; Haniah, Haniah (Universitas Al Azhar Indonesia, 2025)
This study explores the dynamics of tashbīh in Arabic rhetoric, tracing its evolution from a direct classical form to a more imaginative and symbolic modern style. Tashbīh now serves as a medium for expressing inner emotions, social criticism, and ideological values. Using a qualitative-descriptive method and content analysis of modern poetry and prose texts, the study finds that tashbīh comparisons are often implicit and open to multiple interpretations. This reflects an expansion of aesthetic freedom and the adaptability of tashbīh to cultural contexts and changing times. The study contributes to the field of balāghah by offering deeper insight into the transformation of tashbīh’s functions and forms in the contemporary era.Keywords – Imagination, Rhetoric, Tasybih, Transformation.